Analysis of the Configuration Relationship Between the Morphological Characteristics of Lightning Channels and the Charge Structure Based on the Localization of VHF Radiation Sources - YuRui Li; Yang Zhang; YiJun Zhang; Paul R. Krehbiel (Geophysical Research Letters)
Abstract The lightning channel morphology is closely related to developmental processes, which depends on the charge structure. There is currently a lack of understanding of how lightning channel morphology reveals developmental characteristics and charge structure. Based on the Lightning mapping array radiation source localization data of six lightning flashes, we studied the lightning channel morphology characterization method and obtained the spatial distribution of the fractal dimension (FD). We found that the fractal distribution had a consistent spatial and temporal correspondence with the channel development characteristics. Compared to regions with unidirectional extended channels, regions with more channel branches or direction change of channel development have a larger FD and a higher power density, where horizontal channel development is accelerated. These correspondence features reflect the inhomogeneous presence of pocket charge, which provides a new method to use lightning morphology information to reveal the characteristics of charge level distribution within thunderstorm clouds.